Evaluación de la calidad del agua en la microcuenca del río Pumacunchi, provincia de Cotopaxi, periodo 2022 - Del Pozo Panata, Samantha Yamisley (2022)
The contamination of rivers is a worldwide problem, requiring the application of indices that help determine the quality of the water. The present investigation is oriented towards the evaluation of the water contamination of the Pumacunchi river through the CANADIAN and ICOMI indices for the period from May to July 2022. The parameters considered were: pH, turbidity, arsenic, iron, BOD, COD, fecal coliforms., conductivity, hardness and alkalinity, evaluated at two strategic points located in Chantilín-Saquisilí and Latacunga Wholesale Market. For the CANADIAN index all the parameters were produced, while for the ICOMI index the last 3 parameters considered were handled. The results allowed us to identify that, of the 10 evaluating parameters, only the pH and total hardness are within the Maximum Permissible Limit (LMP) established by the TULSMA for water for human consumption and irrigation. While electrical conductivity (694.50 uS/cm), arsenic (0.262 mg/L), iron (5.36 mg/L), BOD (8.19 mg/L), COD (35.17 mg/L), fecal coliforms (138166.66 NMP/100ml) and turbidity (138.22 NTU), exceeded the LMP in the criteria for water for human consumption established by the WHO and the TULSMA in the same way for irrigation water, except for the conductivity remains within the LMP. The CANADIAN index shows that the water quality of the Pumacunchi River is "Bad", for water for human consumption at the two photography points, with an average of 25.5 at point 1 and 20.3 at point 2, while for water irrigated land is also not suitable with an average of 48.8 (point 1) and 39.4 (point 2). In turn, the ICOMI index confirms that the water is of poor quality at the two points of the river with an average of 0.8 (point 1) and 1 (point 2). That is, the river water is not suitable for human consumption, nor for irrigation. These values are quite significant, due to the development of anthropic activities such as the discharge of wastewater without prior treatment, the grazing of animals, etc., which are carried out around it and altering the quality of the water.